Nexus between Carbon Dioxide (CO2) Emission and Energy use in Sri Lanka - Jeyapraba Suresh; Vinayagamoorthy Vasantha (Cita Konsultindo Research Center, 2022)
This study investigates the long-run and short-run relationship between the annual CO2 emission and energy use per person in Sri Lanka. The study applied the Residual Based Test using data from 1985 to 2020. According to the Augmented Dickey-Fuller Test, all the series appear stationary in the first difference for the logarithm form at a 1 per cent significance level. The residual was significant at its level. The results strongly support the conclusion that co-integration between the two variables exists in the long term. The study found a positive relationship between CO2 emission and energy use in Sri Lanka. The fitted model was confirmed through the Normality Test, Serial Correlation Test, Heteroskedasticity Test and Recursive estimates. Error Correction Model (ECM) results found a positive relationship among the variable in the short term. Hence, energy usage is the most critical factor on CO2 emissions. While Sri Lanka has been facing a severe energy crisis in 2022, this study suggests using renewable and alternative energy resources like solar to sustain the environment.